Pengembangan Koleksi Bahan Pustaka di Perpustakaan Batu Api - Aprinur, Rahmatia; Evi Nursanti; Anwar, Rully Khairul (UPT Perpustakaan UIN Alauddin Makassar, 2025)
Private libraries emerged as an alternative when the information needed was not available in formal libraries. Unfortunately, limited resources and the absence of formal written policies made the management of library materials somewhat difficult. The purpose of this study is to analyze collection development activities at the Batu Api Library, a private library located in Jatinangor District, Sumedang. The study uses a qualitative-descriptive method with data collection techniques through observation, interviews, literature study, and documentation study. The results of the study show that the policies used by the Batu Api Library are still informal. The activity of analyzing user needs is also still based on trends. Collection selection emphasizes user needs. Collection acquisition activities are not carried out systematically and still rely on grants. Evaluation and weeding activities are also not carried out regularly, causing the collection to pile up. This study concludes that collection development activities in private libraries mostly do not use written policies. Through this study, it is hoped that private libraries can formulate formal policies, conduct periodic evaluations, and collaborate with institutions to overcome the limitations of resources they face.